What Do Gen Z Students Need to Succeed in Reading Comprehension? - Pramerta, I Gde Putu Agus (VELES Voices of English Language Education Society, 2024)
The development of tailored educational content is essential for meeting the diverse needs of students, particularly in the context of English language education. This study aimed to identify the specific reading requirements of first-year undergraduate students majoring in English language education, focusing on Generation Z, characterized by their digital nativeness and unique learning preferences. Utilizing a mixed-methods approach, the research involved 56 Gen Z students at Mahasaraswati Denpasar University who participated in surveys and semi-structured interviews. The findings revealed a significant preference for intensive reading activities driven by challenges with unfamiliar vocabulary. Additionally, students emphasized the need to improve both vocabulary mastery and reading comprehension skills. The study also identified critical procedural, setting, and role-related needs influencing the learning process. These results underscore the importance of integrating Gen Z students' target and learning needs into the design of reading courses. Consequently, English teachers are encouraged to adapt their instructional strategies based on a comprehensive needs analysis to support their students' learning objectives effectively.